Prevalence of Oral Mucosal Disorders in Diabetes Mellitus Patients Compared with a Control Group - José González-Serrano; Julia Serrano; Rosa María López-Pintor; Víctor Manuel Paredes; Elisabeth Casañas; Gonzalo Hernández (Journal of Diabetes Research)
Chronic hyperglycemia is associated with impaired wound healing and higher susceptibility to infections. It is unclear whether patients with diabetes mellitus (DM) present more oral mucosal disorders compared to control groups. The objectives were to compare (a) the prevalence rates of oral mucosal disorders in the DM and non-DM population and (b) the prevalence rates of specific disorders in the DM and non-DM population. Full-text articles were included if they met the following inclusion criteria: (a) they must be original articles from scientific journals, (b) they must be only cross-sectional studies in English, (c) the prevalence of oral mucosal disorders in DM patients must be evaluated, (d) results must be compared with a healthy control group, and (e) oral mucosal disorders must be specified in DM and non-DM group. All studies showed higher prevalence of oral mucosal disorders in DM patients in relation to non-DM population: 45–88% in type 2 DM patients compared to 38.3–45% in non-DM groups and 44.7% in type 1 DM patients compared to 25% in non-DM population. Tongue alterations and denture stomatitis were the most frequent significant disorders observed. The quality assessment following the Joanna Briggs Institute (JBI) Prevalence Critical Appraisal Tool showed the low quality of the existing studies.